How to improve the durability of composite resin veneers: A literature review (Research, Society and Development, 2024)
Composite resin veneers are widely used in cosmetic dentistry due to the possibility of transforming smiles, correcting imperfections, and improving dental appearance. Their durability depends on several factors. The quality of the materials and the professional skills directly influence the resistance of the veneers, but post-treatment care and patient habits are equally critical. To prolong the useful life of composite resin veneers, preventive maintenance is recommended, including regular visits to the dentist, adequate oral hygiene practices, and avoiding harmful habits such as biting hard objects or grinding the teeth (bruxism). Application techniques are also essential to ensure strong and long-lasting adhesion to the tooth. High-quality adhesives and proper polishing to minimize wear and reduce porosity stand out. Non-abrasive dental hygiene products help keep the appearance and integrity of the resin. This combined care can significantly increase the durability of composite resin veneers, ensuring the patient a beautiful and functional smile for longer.